Análise dos indicadores biométricos e nutricionais da cultura da alface (Lactuca sativa L.) irrigada com água tratada magneticamente utilizando modelagem fuzzy - Putti, Fernando Ferrari [UNESP] (2015)
Current water crises worldwide have caused water rationing, involving urban and rural areas. Several researches have been undertaken to optimize the rational use of water, especially water for irrigation. Researches have recently been conducted on the effects of magnetically treated water for irrigation. Since regression analyses have inherent errors, statistic techniques have been employed to prove the true effects of the experiments and thus more advanced techniques, such as the fuzzy mathematic models, are being used. Current assay analyzes the effects of magnetically treated water in the irrigation of lettuce crops. Fuzzy rules-based models have been developed and results were compared with data collected on the field and with regression models. An experiment was conducted in the Department of Rural Engineering of UNESP, Faculty of Agronomic Sciences, on the Lageado Experimental Farm, Botucatu SP Brazil, to evaluate the development of lettuce crops irrigated with magnetically treated water and with conventional water at different replacement levels based on the culture's evapotranspiration (ETc). Rural Sylocimol equipment, produced by Timol, was employed for the magnetic treatment of water. A randomized block design, with 4 evaluations throughout the cycle, with two cycles, was used. For entrance, the fuzzy systems comprised the irrigation water depths, type of water and time throughout the cycle, whereas biometric and nutritional evaluations were used as exits. Results showed that magnetically treated water provided a significant increase in lettuce crops, whilst decrease in irrigation water volume also occurred. Further, fuzzy models registered a decrease in mean square error...